Factors influencing Brazilian internal auditors' behavioural intention to adopt big data analytics. (23rd June 2021) - Iguma, Marcio Kawahara; Riccio, Edson Luiz
The evolution of internal audit is driven by changes in IT and business environment. Academic literature presented that big data analytics (BDA) represents a paradigm shift but it is not widespread in auditing compared to other fields. A cross-sectional study was conducted to explore the IT tools and data currently in use by 305 internal auditors working in Brazilian private companies and investigates the factors influencing the intention of these professionals to adopt BDA, based on the unified theory of acceptance and use of technology (UTAUT). Data from an online survey were analysed using partial least squares structural equation modelling (PLS-SEM) with an R 2 of 63.1%. The results revealed performance expectancy and social influence as the two key drivers for increasing the likelihood of BDA adoption while effort expectancy and facilitating conditions showed no significant effect. Our findings provide insights for practitioners and researchers to advance this research stream.